Women’s Dissatisfaction toward Their Own Bodies in Breasts and Eggs by Mieko Kawakami (2020) - Fitri, Rahma Annisa; Wahyuni, Delvi (Universitas Negeri Padang, 2024)
This research is an analysis of a novel entitled Breasts and Eggs (2020) by Mieko Kawakami. This research aims to find out how women’s body dissatisfaction is portrayed in the novel. This research is descriptive qualitative research which uses body image and feminist lens to analyze the issues of this research. This research indicates that the novel shows three aspects of body dissatisfaction which are: negative self perception of body shape, negative comparative perception of body image, and negative attitude concerning body image alteration experienced by some of the female characters. This research also indicates that patriarchal culture influences the creation of beauty standards through two things. The first one is through the media that promotes women in sexy figure. The second one is in the work place in which the men prefer Jiang Li with youthful appearance rather than Suzuka who is talented. In conclusion, Body dissatisfaction that is experienced commonly by women cannot be separated from the beauty standard created by patriarchal culture.